2018
DOI: 10.1038/s41409-018-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of sequential treatment of sclerotic chronic graft versus host disease with rituximab and nilotinib

Abstract: Sclerotic chronic graft vs. host disease (cGVHD) still has a large impact on morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). We performed the first prospective study to test whether sequential therapy of the anti-CD20 antibody rituximab followed by 6 months treatment with tyrosine kinase inhibitor nilotinib is a favorable treatment strategy for patients with sclerotic cGVHD. Twenty-nine patients were included, 24 were available for analysis. We observed objective respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Tregs have a suppressive effect by downregulating the proliferative activity of T-cells [2]. For B-cells, a positive influence on GvHD activity has been noted when using Rituximab, a B-cell-depleting antibody [36]. Rituximab was originally developed to treat non-Hodgkin lymphomas [4, 7] but is successful in a variety of autoimmune diseases as well [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tregs have a suppressive effect by downregulating the proliferative activity of T-cells [2]. For B-cells, a positive influence on GvHD activity has been noted when using Rituximab, a B-cell-depleting antibody [36]. Rituximab was originally developed to treat non-Hodgkin lymphomas [4, 7] but is successful in a variety of autoimmune diseases as well [8].…”
Section: Introductionmentioning
confidence: 99%
“…No data suitable for the study criteria were found for dasatinib. One prospective study was found on nilotinib, and it was given sequentially with rituximab [38].…”
Section: Imatinibmentioning
confidence: 99%
“…Binding of rituximab to CD20 results in destruction of the lymphocytes by several mechanisms, including antibody-dependent cell-mediated cytotoxicity, complement-dependent cytotoxicity and direct apoptosis ( 124 , 125 ). It is usually employed at 375 mg/m 2 weekly for four doses; it represents the mAb that is most frequently employed in cGvHD treatment ( 126 128 ), including Scl-cGvHD ( 129 ) in addition to other types of cGvHD ( 37 , 130 , 131 ). Recently, it has been reported that rituximab offered 41% of responses at 1 year, 69% at 2 years, and 77% at 3 years.…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%
“…Finally, combining B cell depletion with rituximab (375 mg/m 2 , once per week, for 4 weeks) followed by TKI inhibition with nilotinib (200 mg, twice daily, for 6 months) have shown a more profound and long-lasting response (8% CR, 63% PR) with a higher survival rate (96.6% in 1 year) in patients with Scl-cGvHD ( 129 ).…”
Section: Emerging Therapies For Chronic Graft-versus-host Diseasementioning
confidence: 99%